A new extension to the Taste Strips test - Wolf, Axel; Illini, Oliver; Uy, Daniel; Renner, Bertold; Mueller, Christian A. (Rhinology, 2016)
Assessment of gustatory function in human subjects using the 'taste strips' test is an easy and validated procedure. The aim of this study was to extend this test in order to detect subjects with superior gustatory sensitivity.The investigation included 134 subjects (29.5±12.6 years, range 18-84 years) with normal gustatory function. Four concentrations of sweet, sour, salty, and bitter were augmented with additional low concentrations (sweet: 25/12.5 mg/ml sucrose; sour: 27/15 mg/ml citric acid; salty: 6.4/2.6 mg/ml sodium chloride, bitter: 0.15/0.06 mg/ml quinine hydrochloride), resulting in a maximum extended taste score (ETS) of 24.The mean ETS was 14.5 ± 3.2. Specifically, it was 4.5 ± 1.2 for sweet, 2.8 ± 1.0 for sour, 4.0 ± 1.3 for salty, and 3.2 ± 1.2 for bitter. In contrast to the original version of the taste strips test, no ceiling effect was observed. Cluster analysis separated three groups of subjects by ETS, whereas test scores derived from the original four concentrations were insufficient to discriminate the subgroup with higher gustatory sensitivity.The extended taste strips test seems to be a useful tool for the detection of patients with low gustatory thresholds for sweet, sour, salty, or bitter taste.
EVALuna2:8526